ANALISIS PROSEDUR ADMINISTRASI PENJUALAN TUNAI PADA KAPEL STORE MALANG - Adellia Elzai Ratna Sari; Dinda Nabilah Rahmasari; Nilawati Fiernaningsih; Rachma Bhakti Utami (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Procedures are very important to speed up company activities. Implementing cash sales administration procedures is a solution for companies, especially trading companies. This research uses qualitative descriptive research. The data collection methods used were interviews, observation and documentation. The results of this research indicate that cash sales administration procedures at the Kapel Store include: sales order procedures, cash, receipt procedures, goods delivery procedures and cash sales recording procedures.